Upaya Meningkatkan Hasil Belajar PAI dengan Menerapkan Pembelajaran Discovery Learning (DL) pada Siswa Kelas V SD Negeri 12 Cot Girek - Azizah (Medan Resource Center, 2022)
ABSTRACTOne of the efforts that can be made to create an active learning process is to use the right learning model. This research is